Perubahan Sifat Fisikokimia Selama Pengolahan Bawang Putih Tunggal Menjadi Bawang Hitam Menggunakan Rice Cooker - Illah Sailah; Maulana Miladulhaq (Department of Agroindustrial Technology, Bogor Agricultural University, 2021)
Optimum duration of black garlic processing by using simple apparatus is still unclear until now. This research has been done through several stages including pre research, characterization of raw materials, producing black garlic, and observation on the physical and chemical content of black garlic. Characterization of physical and chemical content during processing consist of water content, color, reducing sugar, volatile compound and amino acid content. The results of black garlic characterization showed a decrease in moisture content by 0.92% every 3rd days. The result of measurement of brightness level (L*) on the 3rd to 18th day decreased from 72.59% to 37.07%. The reducing sugar content increased during the heating process until day 15th (29.17%). While the volatile compound decreased from 43.27 μeq/g to 6.99 μeq/g on the 18th day. The best duration of processing is 15 days, and generally, amino acid content remains the same between fresh garlic and black garlic. Keywords: single cloves garlic, black garlic, characteristics of black garlic